2014
DOI: 10.4238/2014.january.28.13
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/NF-κB signaling pathway-mediated and oxLDL-induced up-regulation of LOX-1, MCP-1, and VCAM-1 expressions in human umbilical vein endothelial cells

Abstract: ABSTRACT. This study aimed to investigate the function and signaling pathway of Toll-like receptor 4 (TLR4) in oxidized lowdensity lipoprotein (oxLDL)-induced up-regulated expressions of oxidized LDL receptor 1 (LOX-1), monocyte chemoattractant protein 1 (MCP-1), and vascular cell adhesion molecule 1 (VCAM-1) in human umbilical vein endothelial cells (HUVECs). HUVECs were incubated with different oxLDL concentrations (0, 20, 40, 60, and 80 µg/mL) for 24 and 48 h. The influence of oxLDL on TLR4, LOX-1, MCP- TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 23 publications
(25 reference statements)
1
29
0
1
Order By: Relevance
“…Furthermore, the results revealed that the miR-125b mimic repressed the expression levels of VE-cadherin and ICAM-1, the master regulators of endothelial permeability and leukocyte transendothelial migration, in several vascular beds in the HUVECs. A previous study reported that ox-LDL induces a concentration-dependent upregulation of protein expression levels of MCP-1 and ICAM-1 genes, promoting the atherosclerosis obliterans process (35). The results from the present study demonstrated that miR-125b exhibited significant inhibition of the migratory ability of HAVSMCs, compared with the pre-scramble control.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the results revealed that the miR-125b mimic repressed the expression levels of VE-cadherin and ICAM-1, the master regulators of endothelial permeability and leukocyte transendothelial migration, in several vascular beds in the HUVECs. A previous study reported that ox-LDL induces a concentration-dependent upregulation of protein expression levels of MCP-1 and ICAM-1 genes, promoting the atherosclerosis obliterans process (35). The results from the present study demonstrated that miR-125b exhibited significant inhibition of the migratory ability of HAVSMCs, compared with the pre-scramble control.…”
Section: Discussionsupporting
confidence: 59%
“…LOX-1 mediated signaling has been implicated in the development and progression of cardiovascular diseases 14, 27) . By interacting with ox-LOX-1, LOX-1 acts as a key regulator in activating endothelial cells, promoting the adhesion ability of monocytes to the endothelium, and altering VSMCs phenotype by increasing the levels of inflammatory chemokines and adhesion molecules, including monocyte chemotactic protein 1 (MCP-1), E-selectin, P-selectin, and vascular cell adhesion molecule-1 (VCAM-1) 2830) . In ApoE knockout mice, pretreatment with an anti-LOX-1 antibody partly recovered the endothelial-dependent diastolic dysfunction of the micro coronary artery induced by high-fat diet 31, 32) .…”
Section: Discussionmentioning
confidence: 99%
“…An elevation of plasma oxidized LDL (ox‐LDL) is a hallmark of atherosclerosis (Zeibig et al , ) and contributes to endothelial dysfunction (Pandey et al , ). This dysfunction is one of the earliest indicators of atherosclerosis and involves numerous changes in endothelial cells, including an up‐regulation of adhesion molecules (Feng et al , ), an increase in their proliferation (Sun et al , ), a down‐regulation of endothelium‐dependent vasodilatation (Yamamoto et al , ) and NO production (Chan et al , ), and modifications of their electrophysiological properties (Kuhlmann et al , ). Several biological effects of ox‐LDL are mediated via the lectin‐like ox‐LDL receptor‐1 (LOX‐1), the main receptor for ox‐LDL on the endothelial lining of blood vessels (Pirillo et al , ).…”
Section: Introductionmentioning
confidence: 99%